DAYA TERIMA PROPORSI KACANG HIJAU (PHASEOLUS RADIATA L) DAN BEKATUL (RICE BRAN) TERHADAP KANDUNGAN SERAT PADA SNACK BAR - Vyatri Pricilya; Bambang Wirjatmadi; Merryana Andriani (Media Gizi Indonesia, 2015)
Snack bar is a product made from cereal and nuts that usually consumed between meals. Commercial snack bar contains energy, protein, and ﬁber. The ﬁber content in it is usually 1 gram per 25 grams serving. The ﬁber content is relatively low because food categorized as high ﬁ ber if it has 5 grams per 100 gram products. Therefore, a new innovation to improve its ﬁ ber content is required. Green bean and rice bran are type of food with high ﬁber content that possible to be added in snack bar. The purpose of this research was to determine the acceptability and ﬁ ber content in snack bar. This was true experimental research with complete random design (CRD) with 5 treatments. Organoleptic test to assess acceptability of the snack bar was done by 5 trained panelists and 30 non trained panelists. Fiber contentwas calculated using Indonesia Food Composition Database and also analyzed by proximate test in laboratory. The result showed that formula 3 had the highest score than other formulas. Laboratory result showed ﬁ ber content in formula 3 was 1.98 grams per 25 grams snack bar. The conclusion of this research is the snack bar with proportion of green beans and rice bran has a good acceptability and higher ﬁ ber content compared to commercial snack bar.Keywords: ﬁ ber, green beans, rice bran, snack bar